Adaptation opportunities for water security in Brazil - Pereira, Vânia Rosa; Rodriguez, Daniel Andrés; Coutinho, Sonia Maria Viggiani; Santos, Diogo Victor; Marengo, José Antônio (Sustainability in Debate, 2020)
We sought to identify priorities and adaptation opportunities for water security across the various Brazilian biomes. With ever-growing demand and water-usage, future climate scenarios suggest that further water resources management constraints are to be endured throughout the next two decades. The unbalance between high-quality water demand and availability in a multisectoral usage context (e.g., domestic, industry, agribusiness) highlights the socio-ecological Nexus+ concept’s relevance. In this context, the political and cross-institutional articulation and flexibility play a significant role in steering adaptative actions. These challenges in defining action plans, adequately addressed at a multiscale level with inherent climatic uncertainties, are yet to be overcome in Brazilian water resources management. Â